PENGEMBANGAN MODEL LATIHAN FISIK DAN PSIKOLOGI UNTUK MENINGKATKAN PERFORMANCE PEMAIN SEPAKBOLA - Asep Angga Permadi, - (2021)
The purpose of this research is the development of a physical training model in the form of animated videos as a support for individual training to improve the performance of football players. The method used in this study is Research and Development / R & D. Football training which consists of physical, technical, tactical and mental as a whole is a complementary unity. In this research, the authors limit the discussion only related to the development of a physical training model according to the player positions and psychological training (mental) which are implemented in the experiment, according to the urgency for improving the performance of football players. This research was conducted at the Garut Regency PSSI Association. The process of developing a training model involved football experts and coaches with a needs analysis used the Fitness Tests for Football instrument, Bobby Charlton's football skills test, as well as two additional instruments in the form of a Mental Skills Test - football questionnaire, and a football performance evaluation test. Based on the research results obtained from the development of physical training models according to football player positions, namely goalkeeper, defender, midfielder, and forward in the form a 3D animated video with training material based on the duties and functions of individual players used the TacticalPad application with experts validation., all of experts were declared valid. The effectiveness of the training model from small group trial in average result of 17.56 and large group trial in average result of 17.34, if compared with the interval value of 14.66, this means that the trial test results are higher than the interval value so that it is declared suitable or effective for use. There is an effect of the training model according to football player positions and psychological (mental) training with general training on the physical condition of football players with a mean rank value in the control group is 12.0 while the experimental group is 35.0, so that the experimental group has better physical test results. There is an effect of the training model in accordance with the role and psychological (mental) training with general training on football players skill with a mean rank value in the control group is 15.3 while the experimental group is 31.7, so that the experimental group has better skill test results. There is an effect of the training model according to football player positions and psychological training (mental) with general training on the psychology (mental) of football players with a mean rank value in the control group is 12.17 while the experimental group is 34.83, so that the experimental group has better mental test results. There is an effect of the training model according to football player positions and psychological (mental) training with general training on the performance of football players with a mean rank value in the control group of 12.00 while the experimental group is 35.0 so that the experimental group has better performance results. Kata Kunci: Training Model, Physical Condition, Psychology / Mental, Performance, Football Player.